2022
DOI: 10.1055/s-0042-1757692
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian practice guidelines for stroke rehabilitation: Part II

Abstract: The Brazilian Practice Guidelines for Stroke Rehabilitation – Part II, developed by the Scientific Department of Neurological Rehabilitation of the Brazilian Academy of Neurology (Academia Brasileira de Neurologia, in Portuguese), focuses on specific rehabilitation techniques to aid recovery from impairment and disability after stroke. As in Part I, Part II is also based on recently available evidence from randomized controlled trials, systematic reviews, meta-analyses, and other guidelines. Part II covers dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 203 publications
1
8
0
10
Order By: Relevance
“…The study results demonstrate relevance in clinical practice and reaffirm the existing literature, which recommends physical activity after stroke to improve general health and prevent stroke recurrences (Minelli et al, 2022a(Minelli et al, , 2022b, in addition to preventing further injuries to motor and cognitive functionality. Moreover, poststroke physical exercises allow patients to reach the recommended physical activity levels and enhance retention rates in performing exercises (Belfiore et al, 2018), reducing musculoskeletal damages and sarcopenia (Billiot et al, 2020).…”
Section: Variable Inactive Moderately Active Activesupporting
confidence: 82%
See 2 more Smart Citations
“…The study results demonstrate relevance in clinical practice and reaffirm the existing literature, which recommends physical activity after stroke to improve general health and prevent stroke recurrences (Minelli et al, 2022a(Minelli et al, , 2022b, in addition to preventing further injuries to motor and cognitive functionality. Moreover, poststroke physical exercises allow patients to reach the recommended physical activity levels and enhance retention rates in performing exercises (Belfiore et al, 2018), reducing musculoskeletal damages and sarcopenia (Billiot et al, 2020).…”
Section: Variable Inactive Moderately Active Activesupporting
confidence: 82%
“…Recent guidelines also showed that sarcopenia should be tracked with the SARC-F screening tool and considers inactivity as one of the main causes for stroke-related sarcopenia (Minelli et al, 2022a(Minelli et al, , 2022b. In addition, it was reported that physical activity increases muscle strength, motor control, balance, gait, cardiovascular health and reduces osteoporosis in individuals after stroke, once again proving its relevance (Minelli et al, 2022a(Minelli et al, , 2022bYao et al, 2022).…”
Section: Variable Inactive Moderately Active Activementioning
confidence: 99%
See 1 more Smart Citation
“…Existem evidências que a TCI contribui para o aumento da quantidade e da qualidade do uso do membro superior parético nas AVDs (Menezes;Pereira;Dos Anjos, 2023). Os guias, brasileiro e americano, sobre a recuperação e reabilitação do paciente com AVC, indicaram a TCI para esses casos (Minelli et al 2022;Winstein et al 2016). Entretanto, uma das revisões desenvolvidas para comprovar a eficácia da técnica, apontou que a melhora no comprometimento e função motora não reduziu a incapacidade (Minelli et al 2022).…”
Section: Percursos Metodológicosunclassified
“…Os guias, brasileiro e americano, sobre a recuperação e reabilitação do paciente com AVC, indicaram a TCI para esses casos (Minelli et al 2022;Winstein et al 2016). Entretanto, uma das revisões desenvolvidas para comprovar a eficácia da técnica, apontou que a melhora no comprometimento e função motora não reduziu a incapacidade (Minelli et al 2022). Nesse sentido, ressalta-se a necessidade de reforçar os treinos das atividades e de favorecer a transferência dos ganhos obtidos no ambiente clínico para o contexto real de vida do paciente.…”
Section: Percursos Metodológicosunclassified